Pengaruh Pendidikan Kewirausahaan, Manajemen Keuangan Dan Pemasaran Digital Terhadap Minat Berwirausaha Online: Studi Kasus Pada Mahasiswa Di Kota Surakarta - Yoseph Adi Nugroho; Krisna Yusuf Anggoro; Rayhan Gunaningrat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Entrepreneurial, financial management, and digital marketing involve people rising and falling in their entrepreneurial interests online. Variables that affect the interest in online entrepreneurship include financial management, entrepreneurship education, and digital marketing. The study is aimed at seeing how entrepreneurial, financial management, and digital marketing affect entrepreneurship interests online. A sample used of 101 respondents from communities in the city of surakarta, obtained through a dissemination of the questionnaire using Unknown Sampling. Data analysis using IBM SPSS statistics version 25 reveals that through tests of t, they found that an entrepreneurial education (X1) and digital marketing (X3) actually contributed positively to entrepreneurial interest online (Y). However, in the case of a monetary management variable (X2), its significance is 0.196, exceeded the 0.05 significance threshold, Which suggests that financial management (X2) has no significant impact on online entrepreneurial interests (Y).